Parâmetros genéticos, análise de trilha e estratégias de seleção em populações segregantes de soja - Carneiro, Anna Regina Tiago (2020)
The knowledge of the associative behavior between the various characters of economic interest and the different selection strategies enables the successful selection of superior genotypes and expressive selection gains. This thesis was divided into four chapters. The first chapter is the theoretical background that deals with soybean culture, genetic improvement, genetic parameters, path analysis and selection indexes. The second chapter aimed to understand the genetic parameters and selection gains for characters of agronomic importance in three F2soybean populations, in order to carry out a successful selection of superior genotypes. The experiments were carried out in the UFU Soy Genetic Improvement Program, in Uberlândia - MG. Three segregating groups were developed: PSF2-A: BRS256RR x TMG1179RR; PSF2-B: BRS 256RR x UFUS Xavante and PSF2-C: BRS7380RR x TMG1179RR and eleven agronomic characters were formulated. Successful selection of superior genotypes is recommended by the number of days for flowering and plant height at maturity in PSF2-A; for the number of days for flowering, number of seeds per pod, grain production per plant, number of total pods and number of days for maturity in PSF2-B and for the height of insertion of the first pod, number of branched nodes and grain production per plant in PSF2-C. In the third chapter, the objectives were to understand the association between agronomic traits in F2:3transgenicRRsoybean populations through the correlation study and trail analysis in order to enable a successful selection for the genetic improvement of the crop. Two F2:3 segregating populations were sown, PSF2:3-A: BRS256RR x TMG1179RR and PSF2:3-B: BRS7380RR x TMG1179RR. Eight agronomic characters were evaluated. For PSF2:3,the indirect selection for grain production per plant is determined by the number of total pods and for PSF2:3–B,the indirect selection of the number of productive nodes is recommended by the number of nodes at maturity. The number of total pods, in both populations, is useful in the selection of superior progenies in terms of grain yield. In the fourth chapter, the objectives were to verify the genetic potential of agronomic traits and to select soybean F3:4 progenies based on different selection strategies. 123 progenies were sown and the parents, BRS256RR and TMG1179RR and eleven agronomic characters were evaluated. The genetic potential of the F3:4 population is high and allows different selection strategies to be applied to reach superior genotypes. The progenies UFU 72, UFU 116, UFU 86, UFU 45, UFU 117, UFU 56, UFU 5, UFU 106, UFU 6, UFU 4, UFU 73, UFU 101, UFU 96, UFU 90, UFU 123, UFU 116, UFU 88, UFU 65, UFU 70, UFU 3, UFU 69 and UFU 37 were selected by both selection indexes. The UFU 72, UFU 90, UFU 88 and UFU 69 progenies are agronomically superior both in direct and indirect selection, as in Mulamba & Mock (1978) sum of ranks selection indexes and genotype-ideotype.